2021
DOI: 10.1080/10942912.2021.1951290
|View full text |Cite
|
Sign up to set email alerts
|

Water holding capacity and microstructure of sturgeon (Acipenser gueldenstaedti) fillets as affected by low temperature vacuum heating

Abstract: This study was aimed to investigate the effect of low-temperature vacuum heating (LTVH; versus the traditional thermal method-TC -100°C boiling water) on water content/distributions, microstructure, and tenderness of sturgeon fillets. Although all fillets were well done, those fillets heated at lower temperature/time showed higher moisture content (P< .05). Furthermore, microstructure by paraffin section and shear force results also indicated LTVH70-30 (LTVH method; 70°C, 30 min) shown the most similar to TC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…LTVH fillets had higher AGEs concentration than TC fillets, which may be associated with the higher water loss in the TC group treated at 100 °C. And our previous study (Wei et al ., 2021) had reported that the water content decreased significantly in TC fillets. As Li et al .…”
Section: Resultsmentioning
confidence: 99%
“…LTVH fillets had higher AGEs concentration than TC fillets, which may be associated with the higher water loss in the TC group treated at 100 °C. And our previous study (Wei et al ., 2021) had reported that the water content decreased significantly in TC fillets. As Li et al .…”
Section: Resultsmentioning
confidence: 99%
“…The amide A band, which corresponds to the stretching vibrations of hydroxyl O-H and amino N-H bonds, exhibited a shift in frequency from 3290 cm −1 to 3286 cm −1 in the sous-vide treatment group, which indicated a change in hydrogen bonding during the heating process. The absorption peak at 1656 cm −1 corresponds to the stretching vibrations of C=O bonds in the amide I band, which play a crucial role in the formation of secondary structures in myogenic fibers [9]. The intensity of this absorption peak in the amide I band (1655 cm −1 ) was significantly reduced in the spectrum of tilapia fillets treated by conventional high-temperature cooking.…”
Section: Variations In Ftir Spectra Of Tilapia Fillets Subjected To D...mentioning
confidence: 98%
“…The temperature during cooking is crucial for both safety and quality. In a recent study conducted by Wei et al [9], it was discovered that sturgeon fillets treated with boiling water at 60 • C for 15 min under vacuum conditions exhibited the most intact structure when observed via optical microscopy. In addition, the study revealed that the cooking loss of sturgeon treated at 100 • C was significantly higher (33.12% ± 0.46%) than that of sous-vide-treated samples.…”
Section: Introductionmentioning
confidence: 99%